Breastfeeding, Science, and Islam: A Study of Knowledge Among Islamic College Students - Irma Dwi Tantri (Jurnal Studi Gender dan Anak, 2025)
Stunting in early childhood remains a serious problem in Indonesia, one of the main causes of which is suboptimal breastfeeding practices. Breastfeeding is a practice recommended by both science and Islam. Although the majority of Indonesians are Muslim, the rate of exclusive breastfeeding remains low, especially among working and highly educated mothers. This study aims to analyze the knowledge of early childhood Islamic education students, who represent prospective mothers with academic backgrounds in child development and Islamic law. The research uses a mixed-method (convergent) approach. Data was collected through questionnaires and analyzed simultaneously. Findings indicate that while 97% of respondents believe in the superiority of breast milk, only 18% are aware of its immune benefits. All respondents also agreed that the Qur'an encourages breastfeeding, but only 15% could correctly cite the relevant verse. Additionally, many viewed formula milk as the primary solution to breastfeeding challenges and had limited knowledge about maternal nutrition or breastfeeding counseling. These results indicate that while respondents believe in the importance of breastfeeding from both scientific and Islamic perspectives, their understanding is superficial. Therefore, integrated education is needed, involving the government, educational institutions, the community, and religious leaders to strengthen knowledge about breastfeeding among expectant mothers, focusing not only on the benefits of breast milk but also on lactation management. [Stunting pada anak usia dini masih menjadi masalah serius di Indonesia, yang salah satu penyebab utamanya adalah praktik menyusui yang belum optimal. Menyusui merupakan praktik yang dianjurkan baik dalam sains maupun Islam. Meskipun mayoritas penduduk Indonesia beragama Islam, tingkat pemberian ASI eksklusif tetap rendah, terutama di kalangan ibu bekerja dan berpendidikan tinggi. Studi ini bertujuan untuk menganalisis pengetahuan mahasiswa Pendidikan Islam Anak Usia Dini, yang mewakili calon ibu dengan latar belakang akademis tentang perkembangan anak dan syariah Islam. Penelitian ini mengggunakan metode campuran (konvergen). Data dikumpulkan melalui kuesioner dan dianalisis secara bersamaan. Temuan menunjukkan bahwa meskipun 97% responden meyakini keunggulan ASI, hanya 18% yang mengetahui manfaat imunitasnya. Semua responden juga menyetujui bahwa Al-Qur'an menganjurkan praktik menyusui, namun hanya 15% yang dapat menyebutkan ayat tersebut dengan benar. Selain itu, banyak yang menganggap susu formula sebagai solusi utama untuk kendala menyusui dan memiliki pengetahuan yang terbatas tentang nutrisi ibu atau konselor menyusui. Hasil ini menunjukkan bahwa meskipun responden meyakini keutamaan menyusui baik dari perspektif ilmiah dan Islam, pemahaman mereka bersifat dangkal. Oleh karena itu, edukasi terintegrasi diperlukan dengan melibatkan pemerintah, institusi pendidikan, masyarakat, dan tokoh agama untuk memperkuat pengetahuan tentang menyusui di kalangan calon ibu yang tidak hanya berfokus pada keunggulan ASI tetapi juga manajemen laktasi].